2020
DOI: 10.1007/s10755-020-09508-8
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly Publishing at a Crossroads: Scholarly Perspectives on Open Access

Abstract: The cost of access to scholarly research creates inequity for readers with varying resources. Open access publishing is an avenue to address this inequity. This research employed a survey of scholars to discover what they know and think about open access. The survey elicited both faculty and doctoral student perspectives. Data were analyzed according to rank and discipline. Although the majority of scholars across disciplines agreed that their work should be freely available to all readers, there were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Turgut (2021) claims that researchers must go beyond having a basic awareness of OA principles to publish in OA and deposit their work in an OAR. While awareness of OA can be beneficial, the lack of clear understanding of OA principles within discipline-specific publishing knowledge can create false impressions of OA benefits and perceived barriers of OA options (Fitzgerald and Jiang, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Turgut (2021) claims that researchers must go beyond having a basic awareness of OA principles to publish in OA and deposit their work in an OAR. While awareness of OA can be beneficial, the lack of clear understanding of OA principles within discipline-specific publishing knowledge can create false impressions of OA benefits and perceived barriers of OA options (Fitzgerald and Jiang, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Individual traits (i.e. faculty age, rank, status and academic discipline) remain an important factor that can affect faculty participation in OAR (Fitzgerald and Jiang, 2020). According to Casey (2012) faculty in the sciences contribute at a higher degree than do those in the social sciences and humanities.…”
Section: Introductionmentioning
confidence: 99%
“…Fitzgerald and Jiang (2020) state that open access is a way to deal with inequality in relation to the cost for readers to access academic scientific production. In the research they carried out with professors and doctoral students on the subject, they concluded that the majority of scholars from all disciplines agree that their work should be freely available to all.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We highlight articles that reflect what academics know, think and practice with regard to making their scientific production available in this way, and highlight some proposals to increase Open Access (OA) in the academic context. Fitzgerald and Jiang (2020) state that open access is a way to deal with inequality in relation to the cost for readers to access academic scientific production. In the research they carried out with professors and doctoral students on the subject, they concluded that the majority of scholars from all disciplines agree that their work should be freely available to all.…”
Section: Open Access In Higher Educationmentioning
confidence: 99%
“…Thus it is undeniable that work discipline is the determining factor of success in a company; if the discipline of work is ignored will hinder and harm the company (Busta & Russo, 2020;Charity Hudley et al, 2020;Hu & Liu, 2020;Martino, 2020;Rodriguez et al, 2020;Wang et al, 2020). Because without discipline, it will decrease employee performance so that the company's target will not be achieved (Björkhagen Turesson, 2020;Farley-Ripple et al, 2020;Fitzgerald & Jiang, 2020;Martimianakis et al, 2020;Millstein et al, 2020;Rodríguez-Araya et al, 2020).…”
Section: Introductionmentioning
confidence: 99%